2012
DOI: 10.1029/2012ja017767
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric disturbances (infrasound waves) over the Czech Republic excited by the 2011 Tohoku earthquake

Abstract: [1] A train of large amplitude infrasound wave packets was observed by multipoint Continuous Doppler sounding system in the ionosphere over the Czech Republic on 11 March 2011. It is shown that these infrasound wave packets originated from vertical motion of the ground surface that was caused by arrival of seismic waves generated by the strong Tohoku earthquake. The infrasound wave packets were observed in the ionosphere at heights of $210-220 km about 9 min after the detection of corresponding wave packets on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
127
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(134 citation statements)
references
References 43 publications
6
127
0
1
Order By: Relevance
“…The wind field associated with the seismic infrasound at ionospheric altitude transports the ionospheric plasma parallel to the magnetic field and creates perturbations whose features correlate well with that of the infrasound. Recently, Chum et al (2012) found that the features of seismic wave packets observed on the ground using the seismometer matched exactly with the features of the ionospheric response observed using Doppler sounding. The periodicities of the ionospheric perturbations were found to be exactly similar to the Rayleigh wave periodicities.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…The wind field associated with the seismic infrasound at ionospheric altitude transports the ionospheric plasma parallel to the magnetic field and creates perturbations whose features correlate well with that of the infrasound. Recently, Chum et al (2012) found that the features of seismic wave packets observed on the ground using the seismometer matched exactly with the features of the ionospheric response observed using Doppler sounding. The periodicities of the ionospheric perturbations were found to be exactly similar to the Rayleigh wave periodicities.…”
Section: Introductionmentioning
confidence: 76%
“…Chum et al (2012) have also described the infrasound amplification and attenuation in details. The methodology utilized by Chum et al (2012) has been adopted in this study to determine the infrasound amplification and attenuation in the atmosphere. The modelled amplification and attenuation of the infrasound (0.08 Hz) at different height levels with respect to the forcing on the ground is presented next.…”
Section: Propagation Of Seismic Infrasound In the Atmospherementioning
confidence: 99%
See 2 more Smart Citations
“…The dominant seismic wave energy at remote distances is associated with the short-period Airy phase of Rayleigh waves with a period of 10 to 50 s (Oliver, 1962), which propagates over long distances with little dissipation compared to other wave modes. As the excited infrasound signals propagate upward, their amplitudes increase due to the conservation of momentum in the density-rarefied atmosphere (e.g., Chum et al, 2012;Maruyama and Shinagawa, 2014). Infrasound signals with periods longer than ∼ 15 s reach ionospheric altitudes (Tanaka et al, 1984) and interact with ions through neutralion collisions.…”
Section: Introductionmentioning
confidence: 99%